Comparison of Diazepam and Magnesium Sulfate (MgSO₄) Administration in Patients with Eclampsia - Muhammad Rifqi Mudhoffar; Mona Nulanda; Julia Hasir (Journal of Community Health Provision, 2026)
Eclampsia is a serious obstetric complication characterized by seizures in pregnant or postpartum women with preeclampsia and remains a leading cause of maternal morbidity and mortality, particularly in developing countries. Management of eclampsia focuses on the prevention and control of seizures using anticonvulsants, with diazepam and magnesium sulfate (MgSO₄) being the most commonly used drugs. However, the efficacy and safety of these two agents show significant differences. This literature review aims to compare the effectiveness of diazepam and magnesium sulfate (MgSO₄) in patients with eclampsia in terms of seizure prevention, maternal mortality, and maternal and neonatal outcomes. This study employed a literature review design using a narrative review approach. Literature searches were conducted via PubMed, Google Scholar, ScienceDirect, DOAJ, PLOS ONE, BMC, Cureus, and SINTA using keywords related to eclampsia, magnesium sulfate, and diazepam. Relevant research articles from 2020–2025 and textbooks from 2015–2025 were analyzed narratively based on methodological quality and topic relevance. Most studies indicate that MgSO₄ is more effective than diazepam in preventing recurrent seizures, reducing maternal mortality, and yielding better maternal and neonatal outcomes. Diazepam is associated with lower efficacy and a higher risk of adverse effects. Major barriers to the use of MgSO₄ include resource constraints and the readiness of healthcare facilities. Magnesium sulfate (MgSO₄) is the first-line therapy and the gold standard in the management of eclampsia. Strengthening policies, improving the competence of healthcare workers, and ensuring the availability of MgSO₄ must be prioritized to reduce maternal mortality due to eclampsia.